Analisis Proses Pemecahan Masalah Siswa Dalam Mensketsa Luas Daerah Di Bawah Kurva - Nur Azizah; Salwah Salwah; Muhammad Ikram (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2022)
This study aims to analyze the problem solving process of high school students in sketching the integral area under the curve. This research was conducted at SMAN 6 Luwu Timur, South Sulawesi Province. The research method used in this method is a qualitative method using a descriptive approach. The conclusion in this study was that on the engagement indicator it was found that there were students who identified thoroughly and there were also students who only partially identified and there were also students who identified internally. As for the transformation-formulation indicator, it was found that there were students who made initial guesses by using the integral concept first and then guessed the critical points needed to sketch the graph. However, there are also students who make initial guesses by determining the critical points needed to draw the graph first and then in the next guess using the definite integral concept. However, there are also students who only make guesses by guessing critical points by utilizing the available information to sketch graphs. For the implementation indicators, it was found that there were students who formulated the graph first, then created the shaded area of ​​the graph, followed by the calculation phase. Then there are students who only finish at the graph formulation stage making shaded areas on the graph, but do not continue at the calculation phase.